What Did US18 bn Achieve? The 2005 Debt Relief to Nigeria. (5th August 2013) - Dijkstra, Geske
Abstract : Since 2003 Nigeria's economic growth has been consistently above 6% and has been driven by non‐oil sectors. This article attempts to assess the contribution of the 2005 debt‐relief agreement to this higher growth. The agreement eliminated Nigeria's US30 billion debt to Paris Club creditors who cancelled US18 bn, while Nigeria paid back US12 bn. The article traces the three possible impact channels of debt relief, namely, the flow (reduced debt service), the stock (removal of debt overhang) and the conditionality channel, and comes to the conclusion that the debt‐relief agreement played a key role in the country's improved economic performance, in particular through successful conditionality.